Revisando actitudes ante las tecnologías digitales (Innovaciones Educativas, 2021)
Digital technologies have invaded our daily life, work and, of course, our educational system. This raises different behaviors depending on the attitude towards technology. Some range from extreme scaremongering to passive individual opposition. Others lean towards a thoughtful introduction or an uncritical immersion. But in both, we find positions that only show part of the truth. Perhaps we should ask ourselves, as in Justine (Lawrence Durrell) “why don’t people show more than one profile at a time?”
Keywords: Education; digital technologies; innovation; educational technology